Reinforced film-coated geosynthetic clay liner and processing technology

By adopting a reinforced film-type structure and dense needle-punching needle-making process in bentonite waterproof blanket, the problem of unstable waterproof performance in the prior art when the base conditions are poor, and higher waterproof performance and long-term performance are achieved, and suitable for tunnel and water conservancy anti-seepage projects.

CN119704820APending Publication Date: 2025-03-28GUANGDONG XUNKE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411811695.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing bentonite waterproof blankets are difficult to ensure the integrity and long-term waterproofing performance when the base layer conditions are poor, and cannot meet the needs of tunnels and water conservancy anti-seepage projects.

Method used

The reinforced coated bentonite waterproof blanket and processing technology are adopted. The cross-sectional structure consists of HPDE polymer film, non-woven fabric, natural sodium-based bentonite, woven fabric and high-strength braiding fabric. Each layer of materials is closely connected through the dense needle-punching process.

Benefits of technology

The peeling strength, tensile strength and puncture strength of the waterproof blanket are significantly improved, which can better adapt to base layer settlement and pulling and cracking, ensure the integrity and long-term nature of anti-seepage performance, and meet the needs of anti-seepage projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704820A_ABST
    Figure CN119704820A_ABST
Patent Text Reader

Abstract

The invention discloses a reinforced film-coated bentonite waterproof blanket and a processing technology, and relates to the technical field of underground waterproof engineering of basements, tunnels and the like and the technical field of water conservancy anti-seepage engineering of artificial lake water systems, river channels and the like. The section structure of the waterproof blanket sequentially comprises an HPDE polymer film, non-woven fabric, natural sodium bentonite, woven fabric and high-strength woven fabric from top to bottom; the processing method comprises the following processing steps: S1, preparing materials, including 10 to 500 parts of HDPE resin, 10 to 100 parts of an antioxidant, 10 to 150 parts of a stabilizer, 10 to 1000 parts of a non-woven fabric, 10 to 700 parts of natural sodium bentonite raw ore, 100 to 200 parts of a dispersant, 10 to 120 parts of an activator, 100 to 1300 parts of a woven fabric, 10 to 200 parts of carbon fibers, 10 to 150 parts of nano titanium dioxide and 10 to 200 parts of a polyurethane coating. The reinforced film-coated natural sodium bentonite waterproof blanket can adapt to base settlement and resist overall pull-up fracture, and the reinforced film-coated natural sodium bentonite waterproof blanket can better guarantee the integrity of anti-seepage performance in an anti-seepage project, guarantee the integrity and the long-term performance of waterproof performance and meet the requirements of the anti-seepage project.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tunnel anti-seepage engineering, and in particular to a reinforced film-covered bentonite waterproof blanket and a processing technology thereof. Background Art

[0002] Tunnel anti-seepage is a crucial task in tunnel construction, which is related to the long-term stable operation of the tunnel and the safety of the surrounding environment. Long-term leakage may cause the soil behind the tunnel lining to be lost, causing the external pressure on the lining structure to be unevenly distributed, resulting in cracks, deformation and damage, reducing the bearing capacity of the lining structure, and even causing a major safety accident of tunnel collapse in severe cases. If the leaked water enters the tunnel, it will cause erosion to the lighting, communication and power supply facilities in the tunnel, shorten their service life, increase the cost of maintenance and replacement, and may also affect the normal use of these facilities, thereby interfering with the normal operation of the tunnel. In the prior art, there is an anti-seepage waterproof blanket for the construction environment in the tunnel to prevent and control the water seepage problem in the tunnel. The bentonite waterproof blanket uses a needle punching process to tightly combine non-woven fabrics, woven fabrics and bentonite together, which meets the anti-seepage requirements under the correct construction process conditions. Once the base conditions are poor, such as insufficient flatness, insufficient compaction, high risk of later settlement, or the backfill soil cannot meet the design requirements, it is difficult to ensure the integrity and long-term nature of the waterproof performance, and cannot meet the needs of anti-seepage engineering;

[0003] In the field of water conservancy anti-seepage engineering technology such as artificial lake systems and rivers, anti-seepage is crucial in such engineering projects. Referring to the leakage cases of some domestic park lakes, reservoirs and rivers, they have directly caused great economic losses. The performance of existing products is still somewhat insufficient in water conservancy anti-seepage projects, causing leakage in many projects. Once the base conditions are poor, such as insufficient flatness, insufficient compaction, high risk of later settlement, or backfill soil that does not meet the design requirements, it is difficult to ensure the integrity and long-term nature of the waterproof performance, and it cannot meet the needs of anti-seepage projects. In this regard, we have proposed a reinforced coated bentonite waterproof blanket and processing technology. Summary of the invention

[0004] In order to solve the above technical problems, a reinforced film-covered bentonite waterproof blanket and processing technology are provided. This technical solution solves the problem that it is difficult to ensure waterproof performance when the base layer is uneven, settlement occurs in the later stage, and the backfill soil does not meet the standards.

[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is: a reinforced film-coated bentonite waterproof blanket and processing technology, the cross-sectional structure of the waterproof blanket is from top to bottom: HPDE polymer film, non-woven fabric, natural sodium-based bentonite, woven fabric and high-strength woven fabric, and the processing steps are:

[0006] S1. Prepare materials, including 10-500 parts of HDPE resin, 10-100 parts of antioxidant, 10-150 parts of stabilizer, 10-1000 parts of non-woven fabric, 10-700 parts of natural sodium bentonite ore, 100-200 parts of dispersant, 10-120 parts of activator, 100-1300 parts of woven fabric, 10-200 parts of carbon fiber, 10-150 parts of nano titanium dioxide and 10-200 parts of polyurethane coating;

[0007] S2, put HDPE resin, antioxidant and stabilizer into a reaction tank, stir, and heat to 40°C-70°C, melt to obtain liquid rubber, continue mixing and stirring for 13h-20h, and cool to room temperature to obtain base material;

[0008] S3, extruding the base material into an extruder, shearing, plasticizing, stirring and blending at high temperature to obtain a sheet, stretching the sheet, extracting, removing impurities and residual solvents therein, and obtaining an HPDE polymer film after heat setting treatment;

[0009] S4, crushing the natural sodium bentonite ore, adding water to prepare a slurry, and pouring a dispersant and an activator into the slurry to stir and mix, so as to obtain natural sodium bentonite;

[0010] S5. Add carbon fiber and nano-titanium dioxide into the fibers of the woven cloth, and weave the fibers into a high-strength woven cloth using a plain weave method;

[0011] S6. Apply a layer of polyurethane coating on the outer surface of the high-strength woven fabric and wait for it to solidify;

[0012] S7, the obtained HPDE polymer film, non-woven fabric, natural sodium bentonite, woven fabric, high-strength woven fabric, five-layer structure are tightly connected together by dense needle-punching random needle process to obtain a waterproof blanket;

[0013] S8. Cut the waterproof blanket into required lengths, conduct a waterproof test on the waterproof blanket, and package it after passing the test.

[0014] Preferably, the specific materials in step S1 include 450 parts of HDPE resin, 90 parts of antioxidant, 80 parts of stabilizer, 800 parts of non-woven fabric, 550 parts of natural sodium bentonite ore, 110 parts of dispersant, 20 parts of activator, 1200 parts of woven fabric, 160 parts of carbon fiber, 90 parts of nano titanium dioxide and 60 parts of polyurethane coating.

[0015] Preferably, in step S2, the prepared HDPE resin is put into a reaction tank, and antioxidants and stabilizers are added in sequence according to proportion for preliminary stirring. The stirring time is 30 minutes and the heating temperature is 50°C. As the temperature rises, the solid HDPE resin particles begin to soften, and under continuous stirring, they slowly melt into a liquid state and blend more evenly with the antioxidants and stabilizers to form a fluid liquid rubber material, which is continuously stirred. After waiting for the stirring to be completed, it is naturally cooled. During the cooling process, the fluidity of the rubber material slowly decreases and solidifies into a base material.

[0016] Preferably, in step S3, the base material is put into an extruder, sheared, plasticized, stirred and blended at high temperature to obtain a mixed melt, the melt is conveyed to a die head, cooled and solidified on a rapid cooling roller to obtain a sheet, and the sheet is biaxially stretched to improve strength and toughness; the extracted sheet is heat-set to eliminate its internal stress, the heat-set sheet is cleaned to remove surface dirt and impurities, and dried to obtain an HPDE polymer film.

[0017] Preferably, in step S4, the natural sodium bentonite ore is put into a pulverizer for pulverization. After the pulverization is completed, it is placed on a filter screen for filtration to remove large particles of impurities to obtain natural sodium bentonite powder. Water is added to the powder to prepare a slurry. The slurry is continuously stirred during the process of adding water to ensure sufficient dilution. A dispersant and an activator are added during the stirring process for continuous stirring. The stirring time is 1 hour. After the stirring is completed, the natural sodium bentonite is obtained after drying.

[0018] Preferably, in step S5, the nano-titanium dioxide is pre-treated and dispersed, and then the carbon fiber and the fully dispersed nano-titanium dioxide are added to the fiber raw material, and the mixture is stirred and mixed, and then woven.

[0019] Preferably, the weaving process in step S5 adopts a plain weave method, in which the warp yarns and the weft yarns are interwoven with each other in an up-and-down pattern, and the obtained fiber material is pulled and arranged in an orderly manner. The warp yarns are neatly arranged in the longitudinal direction of the weaving machine, and the weft yarns shuttle through them in an orderly manner. Under mechanical weaving, each interweaving of the warp and weft yarns is accurate and correct, and the prototype of the high-strength woven cloth is gradually constructed to form a high-strength woven cloth.

[0020] Preferably, in step S6, the prepared polyurethane coating is transferred to a brushing container. The polyurethane coating includes polyol and isocyanate. A brush is used to apply the coating to the outer surface of the high-strength woven cloth. The polyurethane coating is applied layer by layer, and the excess coating is spread evenly. The coating is completed and waited for solidification.

[0021] Preferably, in step S7, the processed five layers of material are stacked in order from top to bottom, a needle is selected, the needle is a metal needle with a barb, and the diameter is between 0.8 mm and 1.5 mm, the needling machine is started, and the needle plate with the needle starts to reciprocate up and down at the set moving speed and needling frequency, and the stacked five layers of material are subjected to initial needling. After the initial needling, the needle plate angle of the needling machine is adjusted, and the moving path of the needle plate is changed at the same time, and random needling is performed, and the needling is repeated for 3 to 8 times. After the needling is completed, a comprehensive appearance inspection is performed.

[0022] Preferably, the waterproof test in step S8 includes a hydrostatic pressure test, a permeability coefficient test and an immersion test.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The performance indicators of the present invention are significantly improved compared with existing products, such as peel strength, tensile strength, puncture strength, etc.; the HDPE polymer film plays an auxiliary waterproofing role, the non-woven fabric provides HDPE adhesion and undertakes the expansion stress of natural sodium-based bentonite. Natural sodium-based bentonite forms a high-density colloid after absorbing water when it meets water, and plays a main anti-seepage role. Ordinary woven cloth is weak in bearing the expansion stress of natural sodium-based bentonite and can only adapt to slight settlement. The high-strength woven cloth protects the integrity of the waterproof blanket material during the entire actual construction stage to avoid damage by foreign matter or protrusions in the base layer, adapts to the settlement of the base layer, and resists overall pulling and rupture. The reinforced coated natural sodium-based bentonite waterproof blanket can better ensure the integrity of the anti-seepage performance in anti-seepage projects, ensure the integrity and long-term nature of the waterproof performance, and meet the needs of anti-seepage projects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a cross-sectional structural diagram of the reinforced film-coated bentonite waterproof blanket of the present invention. DETAILED DESCRIPTION

[0026] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0027] Reference Figure 1 As shown, a reinforced film-coated bentonite waterproof blanket and its processing technology, the cross-sectional structure of the waterproof blanket from top to bottom is: HPDE polymer film, non-woven fabric, natural sodium-based bentonite, woven fabric and high-strength woven fabric, and its processing steps are:

[0028] S1. Prepare materials, including 10-500 parts of HDPE resin, 10-100 parts of antioxidant, 10-150 parts of stabilizer, 10-1000 parts of non-woven fabric, 10-700 parts of natural sodium bentonite ore, 100-200 parts of dispersant, 10-120 parts of activator, 100-1300 parts of woven fabric, 10-200 parts of carbon fiber, 10-150 parts of nano titanium dioxide and 10-200 parts of polyurethane coating;

[0029] S2, put HDPE resin, antioxidant and stabilizer into a reaction tank, stir, and heat to 40°C-70°C, melt to obtain liquid rubber, continue mixing and stirring for 13h-20h, and cool to room temperature to obtain base material;

[0030] S3, extruding the base material into an extruder, shearing, plasticizing, stirring and blending at high temperature to obtain a sheet, stretching the sheet, extracting, removing impurities and residual solvents therein, and obtaining an HPDE polymer film after heat setting treatment;

[0031] S4, crushing the natural sodium bentonite ore, adding water to prepare a slurry, and pouring a dispersant and an activator into the slurry to stir and mix, so as to obtain natural sodium bentonite;

[0032] S5. Add carbon fiber and nano-titanium dioxide into the fibers of the woven cloth, and weave the fibers into a high-strength woven cloth using a plain weave method;

[0033] S6. Apply a layer of polyurethane coating on the outer surface of the high-strength woven fabric and wait for it to solidify;

[0034] S7, the obtained HPDE polymer film, non-woven fabric, natural sodium bentonite, woven fabric, high-strength woven fabric, five-layer structure are tightly connected together by dense needle-punching random needle process to obtain a waterproof blanket;

[0035] S8. Cut the waterproof blanket into required lengths, conduct a waterproof test on the waterproof blanket, and package it after passing the test.

[0036] This application selects a variety of materials with different functions. HDPE resin is used as the main structural material to provide basic strength and shape retention. Antioxidants and stabilizers can effectively protect the material from oxidation, light and heat factors during processing and subsequent use, and extend the service life of the product. Non-woven fabrics can increase the overall flexibility and cushioning, and to a certain extent, help improve the waterproof performance. The natural sodium bentonite ore has excellent water absorption, swelling and anti-seepage capabilities after treatment. Woven fabrics and high-strength woven fabrics further enhance the overall mechanical strength, making it more durable. Carbon fiber and nano-titanium dioxide are used to enhance strength. Polyurethane coatings are used for surface protection and to enhance comprehensive performance. These materials work together to make the final waterproof blanket have a variety of excellent properties, meeting the needs of waterproofing, strength, and durability in different scenarios.

[0037] By precisely controlling the stirring, heating temperature and stirring time parameters in the reaction tank, the antioxidant and stabilizer can be evenly dispersed in the HDPE resin, giving full play to their protective role, ensuring that the subsequent processing and the final polymer film have stable performance during long-term use, and are not prone to performance degradation due to oxidation and aging problems, thereby improving the reliability of product quality;

[0038] The natural sodium bentonite ore is crushed, water is added to make a slurry, and a dispersant and an activator are added and stirred to help remove impurities in the ore and increase the content of effective ingredients in the bentonite. At the same time, the activator can further optimize the performance of the bentonite and enhance its water absorption, expansion and ion exchange capacity;

[0039] Carbon fiber and nano-titanium dioxide are added to the woven fabric fibers. Carbon fiber has ultra-high strength and modulus, and nano-titanium dioxide relies on its microscopic properties to enhance fiber interaction. The synergistic effect of the two can greatly improve the tensile and tear strength of the woven fabric. When the waterproof blanket is subjected to external forces such as stretching and tearing, the high-strength woven fabric inside can effectively resist and avoid structural damage, thus ensuring the integrity and durability of the waterproof blanket.

[0040] The five layers of materials are tightly connected together using a dense needle-punching process, so that the layers form an organic whole through the mutual entanglement of fibers and the filling and bonding effect of bentonite.

[0041] The specific materials in step S1 include 450 parts of HDPE resin, 90 parts of antioxidant, 80 parts of stabilizer, 800 parts of non-woven fabric, 550 parts of natural sodium bentonite ore, 110 parts of dispersant, 20 parts of activator, 1200 parts of woven fabric, 160 parts of carbon fiber, 90 parts of nano titanium dioxide and 60 parts of polyurethane coating.

[0042] In step S2, the prepared HDPE resin is put into the reaction tank, and antioxidants and stabilizers are added in sequence according to the proportion for preliminary stirring. The stirring time is 30 minutes and the heating temperature is 50°C. As the temperature rises, the solid HDPE resin particles begin to soften. Under the continuous stirring, they slowly melt into liquid and blend more evenly with the antioxidants and stabilizers to form a fluid liquid rubber material, which is continuously stirred. After waiting for the stirring to be completed, it is naturally cooled. During the cooling process, the fluidity of the rubber material gradually decreases and solidifies into a base material.

[0043] After adding the HDPE resin, the present application adds the antioxidant and the stabilizer in proportion and performs preliminary stirring for 30 minutes, so that the newly added antioxidant and stabilizer can be initially dispersed among the resin particles. The heating temperature of 50°C is just right. This temperature is in the appropriate range for the HDPE resin to soften and gradually melt. If the temperature is too low, the softening and melting process of the resin will become extremely slow or even difficult to achieve, resulting in the inability to stir smoothly to evenly mix the various components, affecting the quality of the rubber compound; and if the temperature is too high, the resin may be excessively degraded and its performance may be impaired, or the antioxidant and stabilizer additives may be decomposed and rendered ineffective due to the high temperature.

[0044] In step S3, the base material is put into an extruder, sheared, plasticized, stirred and blended at high temperature to obtain a mixed melt, the melt is conveyed to a die head, cooled and solidified on a rapid cooling roller to obtain a sheet, and the sheet is biaxially stretched to improve strength and toughness; the extracted sheet is heat-set to eliminate its internal stress, the heat-set sheet is cleaned to remove surface dirt and impurities, and dried to obtain an HPDE polymer film.

[0045] After the base material of the present application enters the extruder, it is driven by the rotation of the screw and is subjected to shear force. This shear force can break and refine the larger particles or agglomerated base materials that may have existed originally, making the particle size of the material more uniform. The plasticization process under high temperature gradually transforms the solid base material into a melt state with good fluidity, making the material softer and easier to process and shape. After the melt is transported to the die head, it is cooled and solidified on a rapid cooling roller, which can quickly transform the fluid melt into a solid sheet.

[0046] In step S4, the natural sodium bentonite ore is put into a pulverizer for pulverization. After the pulverization is completed, it is placed on a filter screen for filtration to remove large particles of impurities to obtain natural sodium bentonite powder. Water is added to the powder to prepare a slurry. During the process of adding water, the slurry is continuously stirred to ensure sufficient dilution. During the stirring process, a dispersant and an activator are added for continuous stirring. The stirring time is 1 hour. After the stirring is completed, the slurry is dried to obtain the natural sodium bentonite.

[0047] The present application places the crushed material on a filter screen for filtration, which can effectively screen out large particle impurities, such as stones mixed in the original ore, inadequately crushed lumps and other mineral impurities. If these large particle impurities remain in the natural sodium-based bentonite, they will not only affect its purity and reduce the relative content of its effective ingredients, but may also become a weak point in subsequent applications. The dispersant can be adsorbed on the surface of the bentonite particles, and through the electrostatic repulsion and steric hindrance mechanism, the particles repel each other, effectively preventing them from reaggregating in the slurry.

[0048] In step S5, the nano titanium dioxide is pre-treated and dispersed, and then the carbon fiber and the fully dispersed nano titanium dioxide are added to the fiber raw material, and the mixture is stirred and mixed, and then woven.

[0049] The nano-titanium dioxide in the present application has a very small particle size, a very high specific surface area and surface energy, and is very easy to agglomerate under normal conditions to form larger aggregates. The carbon fiber itself has excellent properties of ultra-high strength, modulus and extremely small deformation rate. After dispersion, the nano-titanium dioxide can enhance the interaction between fibers from a microscopic perspective. When added to the fiber raw material, the two can play a synergistic role. Stirring and mixing the mixture to which the carbon fiber and nano-titanium dioxide are added can make the two reinforcing materials evenly distributed in the fiber raw material.

[0050] The weaving process in step S5 adopts plain weave, in which the warp yarns and weft yarns are interwoven in an up-and-down pattern. The obtained fiber material is pulled and arranged in an orderly manner. The warp yarns are neatly arranged in the longitudinal direction of the weaving machine, and the weft yarns shuttle through them in an orderly manner. Under mechanical weaving, each interweaving of the warp and weft yarns is accurate and correct, gradually building up the prototype of high-strength woven cloth to form a high-strength woven cloth.

[0051] The plain weave of the present application is achieved by interweaving the warp yarns and the weft yarns in an up-and-down pattern, so that the woven cloth forms a regular, orderly and tight structure. Since the warp and weft yarns of the plain weave are interwoven evenly and regularly, when the woven cloth is subjected to external force, the force can be evenly dispersed along the yarns and transmitted to the entire woven cloth structure. The regular interweaving method of the plain weave is relatively simple and easy to be accurately operated by machinery. Under the action of the weaving machine, the warp yarns and the weft yarns can be interwoven in an orderly manner according to the set program. Each interweaving of the warp and weft yarns can be done accurately and without error, which greatly improves production efficiency and can ensure that each piece of high-strength woven cloth produced has highly consistent quality and performance, which is convenient for large-scale industrial production and meets the market demand for product quantity and quality stability.

[0052] In step S6, the prepared polyurethane coating is transferred to a coating container. The polyurethane coating includes polyol and isocyanate. A brush is used to apply the coating to the outer surface of the high-strength woven cloth. The polyurethane coating is applied layer by layer, and the excess coating is spread evenly. The coating is completed and waited for solidification.

[0053] The present application transfers the prepared polyurethane coating to a painting container. This operation helps to keep the coating in a good usable state. During the painting process, local coating accumulation and slightly thick thickness are inevitable. The operation of evenly spreading the excess coating can effectively avoid a series of problems caused by uneven coating thickness. Waiting for the painted polyurethane coating to solidify is a key process for converting the coating from liquid to solid, thereby forming a stable and solid protective layer on the surface of the high-strength woven cloth.

[0054] In step S7, the processed five layers of material are stacked in order from top to bottom, and a needle is selected. The needle is a metal needle with a barb and has a diameter of 0.8mm-1.5mm. The acupuncture machine is started, and the needle plate with the needle starts to move up and down at the set moving speed and acupuncture frequency. The stacked five layers of material are subjected to initial acupuncture. After the initial acupuncture, the needle plate angle of the acupuncture machine is adjusted, and the moving path of the needle plate is changed at the same time. Random needle acupuncture is performed, and the acupuncture is repeated for 3-8 times. After the acupuncture is completed, a comprehensive appearance inspection is performed.

[0055] After completing the initial needling, the present application adjusts the angle of the needle plate of the needling machine and changes its moving path to perform random needling. This practice is of great significance. The initial needling mainly establishes the connection between the materials in the vertical direction, while random needling enables the needles to penetrate the material from multiple different directions by changing the angle and irregular moving path, so that the fibers in each layer of material can be further entangled with each other in horizontal, inclined and more different directions. This can avoid the problem of materials being connected only in a single vertical direction and having weak links in other directions, so that each layer of material forms a more compact, stable and all-round connected overall structure.

[0056] The waterproof test in step S8 includes hydrostatic pressure test, permeability coefficient test and immersion test.

[0057] The waterproof testing methods in this application are all existing technologies and will not be described in detail here.

[0058] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.

Claims

1. A reinforced film-covered bentonite waterproof blanket and a processing technology, characterized in that: The cross-sectional structure of the waterproof blanket from top to bottom is: HPDE polymer film, non-woven fabric, natural sodium-based bentonite, woven fabric and high-strength woven fabric. The processing steps are: S1. Prepare materials, including 10-500 parts of HDPE resin, 10-100 parts of antioxidant, 10-150 parts of stabilizer, 10-1000 parts of non-woven fabric, 10-700 parts of natural sodium bentonite ore, 100-200 parts of dispersant, 10-120 parts of activator, 100-1300 parts of woven fabric, 10-200 parts of carbon fiber, 10-150 parts of nano titanium dioxide and 10-200 parts of polyurethane coating; S2, put HDPE resin, antioxidant and stabilizer into a reaction tank, stir, and heat to 40°C-70°C, melt to obtain liquid rubber, continue mixing and stirring for 13h-20h, and cool to room temperature to obtain base material; S3, extruding the base material into an extruder, shearing, plasticizing, stirring and blending at high temperature to obtain a sheet, stretching the sheet, extracting, removing impurities and residual solvents therein, and obtaining an HPDE polymer film after heat setting treatment; S4, crushing the natural sodium bentonite ore, adding water to prepare a slurry, and pouring a dispersant and an activator into the slurry to stir and mix, so as to obtain natural sodium bentonite; S5. Add carbon fiber and nano-titanium dioxide into the fibers of the woven cloth, and weave the fibers into a high-strength woven cloth using a plain weave method; S6. Apply a layer of polyurethane coating on the outer surface of the high-strength woven fabric and wait for it to solidify; S7, the obtained HPDE polymer film, non-woven fabric, natural sodium bentonite, woven fabric, high-strength woven fabric, five-layer structure are tightly connected together by dense needle-punching random needle process to obtain a waterproof blanket; S8. Cut the waterproof blanket into required lengths, conduct a waterproof test on the waterproof blanket, and package it after passing the test.

2. A reinforced film-covered bentonite waterproof blanket and processing technology according to claim 1, characterized in that: The specific materials in step S1 include 450 parts of HDPE resin, 90 parts of antioxidant, 80 parts of stabilizer, 800 parts of non-woven fabric, 550 parts of natural sodium bentonite ore, 110 parts of dispersant, 20 parts of activator, 1200 parts of woven fabric, 160 parts of carbon fiber, 90 parts of nano titanium dioxide and 60 parts of polyurethane coating.

3. A reinforced film-covered bentonite waterproof blanket and processing technology according to claim 1, characterized in that: In step S2, the prepared HDPE resin is put into the reaction tank, and antioxidants and stabilizers are added in sequence according to the proportion for preliminary stirring. The stirring time is 30 minutes and the heating temperature is 50°C. As the temperature rises, the solid HDPE resin particles begin to soften. Under the continuous stirring, they slowly melt into liquid and blend more evenly with the antioxidants and stabilizers to form a fluid liquid rubber material, which is continuously stirred. After waiting for the stirring to be completed, it is naturally cooled. During the cooling process, the fluidity of the rubber material gradually decreases and solidifies into a base material.

4. The reinforced film-covered bentonite waterproof blanket and processing technology according to claim 1, characterized in that: In step S3, the base material is put into an extruder, sheared, plasticized, stirred and blended at high temperature to obtain a mixed melt, the melt is conveyed to a die head, cooled and solidified on a rapid cooling roller to obtain a sheet, and the sheet is biaxially stretched to improve strength and toughness; The extracted sheet is heat-set to eliminate the internal stress, the heat-set sheet is cleaned to remove the dirt and impurities on the surface, and dried to obtain the HPDE polymer film.

5. The reinforced film-covered bentonite waterproof blanket and processing technology according to claim 1, characterized in that: In step S4, the natural sodium bentonite ore is put into a pulverizer for pulverization. After the pulverization is completed, it is placed on a filter screen for filtration to remove large particles of impurities to obtain natural sodium bentonite powder. Water is added to the powder to prepare a slurry. During the process of adding water, the slurry is continuously stirred to ensure sufficient dilution. During the stirring process, a dispersant and an activator are added for continuous stirring. The stirring time is 1 hour. After the stirring is completed, the slurry is dried to obtain the natural sodium bentonite.

6. The reinforced film-covered bentonite waterproof blanket and processing technology according to claim 1, characterized in that: In step S5, the nano titanium dioxide is pre-treated and dispersed, and then the carbon fiber and the fully dispersed nano titanium dioxide are added to the fiber raw material, and the mixture is stirred and mixed, and then woven.

7. The reinforced film-covered bentonite waterproof blanket and processing technology according to claim 1, characterized in that: The weaving process in step S5 adopts plain weave, in which the warp yarns and weft yarns are interwoven in an up-and-down pattern. The obtained fiber material is pulled and arranged in an orderly manner. The warp yarns are neatly arranged in the longitudinal direction of the weaving machine, and the weft yarns shuttle through them in an orderly manner. Under mechanical weaving, each interweaving of the warp and weft yarns is accurate and correct, gradually building up the prototype of high-strength woven cloth to form a high-strength woven cloth.

8. The reinforced film-covered bentonite waterproof blanket and processing technology according to claim 1, characterized in that: In step S6, the prepared polyurethane coating is transferred to a coating container. The polyurethane coating includes polyol and isocyanate. A brush is used to apply the coating to the outer surface of the high-strength woven cloth. The polyurethane coating is applied layer by layer, and the excess coating is spread evenly. The coating is completed and waited for solidification.

9. The reinforced film-covered bentonite waterproof blanket and processing technology according to claim 1, characterized in that: In step S7, the processed five layers of material are stacked in order from top to bottom, and a needle is selected. The needle is a metal needle with a barb and has a diameter of 0.8mm-1.5mm. The acupuncture machine is started, and the needle plate with the needle starts to move up and down at the set moving speed and acupuncture frequency. The stacked five layers of material are subjected to initial acupuncture. After the initial acupuncture, the needle plate angle of the acupuncture machine is adjusted, and the moving path of the needle plate is changed at the same time. Random needle acupuncture is performed, and the acupuncture is repeated for 3-8 times. After the acupuncture is completed, a comprehensive appearance inspection is performed.

10. The reinforced film-covered bentonite waterproof blanket and processing technology according to claim 1, characterized in that: The waterproof test in step S8 includes hydrostatic pressure test, permeability coefficient test and immersion test.